Family Vegetable Garden Manual (Ediciones INTA, 2023)
The 2014 Ebola outbreak in West Africa has affected our countries not only from a sanitary but also from a socio-economic point of view. Increment on food prices, food scarcity and hunger are some of the unwelcomed consequences of the Ebola pandemic. Families and indeed entire communities are facing now those challenges with hope and creativity. We would like to present one more initiative which we call the "Family Vegetable Garden" Programme. This programme was created in Argentina by INTA (National Institute of Agricultural Technology) and implemented in several countries in order to improve food production and for the feeding of hundreds of thousands of families, especially in countries which were facing natural disasters and calamities. The main aim of this programme is therefore to improve food security, increasing availability, accessibility and production of food with an agro-ecological approach. It fosters the participation and organization of our communities to that aim so that they become protagonists in a gradual process of social and economic growth. Specific objectives of this programme are: • To better and diversify the feeding of families, schools and community organizations. • To increase food production and the income of the beneficiaries of the programme. • To promote the participation of the community in food production. • To spread appropriate technologies to produce vegetables and crops. • To promote alternative activities for food production integrated in a market view where the person and the families are at the centre. This initiative is highly relevant for our countries because it fosters the local production of food utilizing appropriate technologies which care for the environment and securing at the same time access to appropriate nutritious feeding for all those who are suffering the socio economic consequences of the Ebola outbreak. In this booklet you will find how to improve your family feeding, what to do in order to start your garden cultivation of crops, which resources are needed, how to improve the fertility of the soil, how to plan the sowing, how to produce seeds and seedlings and how to care for the items and products of the soil. Our gratitude to all those who authorized the use of these materials, those who worked in the translation and designing of the booklet. A big thanks to all those who believe in this programme and have contributed to implement it in our countries!